Analyzing the Lived Experiences of University Managers in Iraq in the Context of Knowledge Management Implementation to Propose a Model - Doleh Khalifeh, Ali; Shafiepour Motlagh, Farhad; Yunus Al Jabar, Raed Rasem; Saeidian, Narges (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2025)
Objective: The aim of this research was to analyze the lived experiences of university managers in Iraq regarding the implementation of knowledge management to propose a model. Methodology: The research methodology was qualitative-phenomenological. The research environment included all university managers in Iraq during the years 2023-2024. The sampling method was purposive and continued to the point of theoretical saturation until sufficient information was obtained, resulting in 21 university managers in Iraq. The research tools were in-depth and unstructured interviews. To determine the validity and reliability of the codes extracted from the interviews, the expert consensus method was used for confirmability. Data analysis was performed using open coding, axial coding, and selective coding. Findings: The results showed that the model for analyzing the lived experiences of university managers in Iraq regarding knowledge management implementation comprises eight dimensions: organizational structure reconstruction, organizational welfare, organizational technology, promotion of organizational leadership culture, organizational excellence, organizational knowledge processing, overcoming limitations, and enhancing stakeholder service quality. Conclusion: The findings of this study underscore the critical importance of various dimensions in the effective implementation of knowledge management in Iraqi universities. These dimensions include the reconstruction of organizational structure, enhancement of organizational welfare, utilization of organizational technology, promotion of organizational leadership culture, and processing of organizational knowledge. Additionally, addressing organizational constraints and improving stakeholder service quality are essential for fostering an environment conducive to knowledge management.